Die Problembereiche und Zweifelsfragen bei der Umsetzung der Regelungen zur Bekämpfung von hybriden Gestaltungen - Lepsien, Virginia (Young Academics: Internationales Steuerrecht, 2023)
Section 4k EStG introduced rules to combat hybrid arrangements. Many important questions remain unanswered. Virginia Lepsien examines the questions of interpretation of § 4k EStG and critically questions whether the legislator has achieved its original goal with this legal norm. In doing so, she analyses undefined legal concepts and conflicts of norms with existing regulations. In addition, she discusses the inconsistencies of imported taxation and the taxpayer's duty to cooperate.